PENGEMBANGAN KURIKULUM PEMBELAJARAN BERBASIS PROYEK DALAM MENINGKATKAN KETERAMPILAN PESERTA DIDIK - Asriani Putri; Afina; Nadia Sofia Fadilasari; Syevinna Alifia Dinta; Andriesgo, Johan (LP2M IAIN Sultan Amai Gorontalo, 2025)
This study discusses the development of a project-based learning curriculum as a strategy to improve students' skills in facing the challenges of the 21st century. Project-based learning emphasizes the active involvement of students through the completion of real projects that encourage the development of critical thinking skills, creativity, collaboration, and communication. This approach is designed so that the curriculum focuses on projects as the core of learning, and emphasizes constructive investigation, student autonomy, and the contextual relevance of the project. The study uses a literature study method to analyze the principles, design, implementation, and evaluation of project-based learning. The results of the study indicate that this model is effective in improving students' motivation, problem-solving skills, and active participation. Despite challenges such as limited resources and uneven distribution of work, project-based learning provides great opportunities in shaping students' character and connecting learning with social reality.